Correction: Corrigendum: Impaired protein translation in Drosophila models for Charcot–Marie–Tooth neuropathy caused by mutant tRNA synthetases - Sven Niehues; Julia Bussmann; Georg Steffes; Ines Erdmann; Caroline Köhrer; Litao Sun; Marina Wagner; Kerstin Schäfer; Guangxia Wang; Sophia N. Koerdt; Morgane Stum; Sumit Jaiswal; et al. (Nature Communications, 2016)
Nature Communications 6: Article number: 7520 (2015); Published: 3 July 2015; Updated: 21 January 2016. The authors inadvertently omitted Sumit Jaiswal, who was originally included in the Acknowledgements section of this Article and contributed to the cloning of transgenic constructs and the balancing of transgenic flies, from the author list.